Islamic banking implementation: supportive role of business service - Mohanachandran, Dileep Kumar; Normala, S. Govindarajo (Penerbit Universiti Kebangsaan Malaysia, 2019)
Islamic banking has advanced in the past four decades. It has become a worldwide brand, cultured and structured industry. Nevertheless, Malaysia has witnessed low penetration of Islamic banking. Researchers documented several reasons allied with low market penetration of Islamic banking. Although Malaysian industrial sector is dominated by Small and Medium Enterprises, there is less information about small business owner’s intention to adopt Islamic banking. Following the Theory of Reasoned Action, this research includes attitude, social influence and business service factors effect on intention to adopt Islamic banking. The research followed positivist research philosophy and quantitative descriptive cross-sectional study design to explicate the relationship between small business owner’s attitude, social influence and business service on intention to adopt Islamic banking. 390 sample from Klang Valley region of Selangor state of Malaysia was considered for the study. Data was collected using survey method through the distribution of structured questionnaires. PLS-SEM was used to test the predictive relevance. The results indicate a strong positive relationship between attitude, social influence and business service on intention to adopt Islamic banking.